2003
DOI: 10.1081/ias-120020085
|View full text |Cite
|
Sign up to set email alerts
|

One Step Enzyme Linked Immunosorbent Assay for Direct Estimation of Serum Testosterone

Abstract: One step competitive enzyme linked immunosorbent assay (ELISA) for direct estimation of testosterone in human serum is described. Testosterone-3-O-carboxymethyl-oxime-bovine serum albumin (testosterone-3-O-CMO-BSA), was used as immunogen and testosterone-3-O-carboxymethyl-oxime-adipic-acid dihydrazide-horseradish peroxidase (testosterone-3-O-CMO-ADH-HRP) was used as tracer. To the testosterone antibody coated microtiter wells, standard or serum samples (100 microL), along with testosterone-3-O-CMO-ADH-HRP conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…However, the discrepancy in results (78 % vs. 90%) may be attributed to difference in methodologies; in the present investigation, we categorized CVB as the variation over a period of ~12 h whereas Valero-Politi and Fuentes-Arderiu [20] measured yearly variation at monthly intervals but only within a 90 min daily window. More importantly, the present investigation utilized ELISA whereas Valero-Politi and Fuentes-Arderiu [20] used radioimmunoassay (RIA), known to exhibit smaller CVA [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the discrepancy in results (78 % vs. 90%) may be attributed to difference in methodologies; in the present investigation, we categorized CVB as the variation over a period of ~12 h whereas Valero-Politi and Fuentes-Arderiu [20] measured yearly variation at monthly intervals but only within a 90 min daily window. More importantly, the present investigation utilized ELISA whereas Valero-Politi and Fuentes-Arderiu [20] used radioimmunoassay (RIA), known to exhibit smaller CVA [18].…”
Section: Discussionmentioning
confidence: 99%
“…Van Weemen and Schuurs [41] observed that hapten and bridge heterology have a lesser effect on sensitivity compared with site-heterologous systems. In later studies, it has been reported that both bridge and hapten heterology improved sensitivity of EIAs for cortisol, [23,35,44] testosterone, [17,45] progesterone, [22,24,46] and DHEA. [34] In these heterologous assays, an EIA becomes specific and sensitive due to the use of structurally different hapten derivatives.…”
Section: Discussionmentioning
confidence: 95%
“…(i) homologous assay and (ii) heterologous assay. In homologous assay, [17][18][19][20] a steroid derivative is the same for the conjugation with carrier protein and enzyme to generate the antibody and to prepare enzyme conjugate; however, the assay is generally less sensitive. [21] On the other hand, in heterologous assay, [22][23][24][25][26][27][28] certain differences of site, bridge, or hapten exist between the steroid derivatives used for immunogen preparation and for the preparation of enzyme conjugate, while the assay is more sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained serum was stored until hormone analysis at -20ºC. The concentration of testosterone in serum was measured in all samples by ELISA technique (Shrivastav et al, 2003).…”
Section: Blood Sampling and Analysismentioning
confidence: 99%